(untitled) (KULT_online, 2021)
Futures Worth Preserving: Cultural Constructions of Nostalgia and Sustainability (eds. Schröder et al.), an edited volume that probes the boundaries of traditional academic anthologies to do justice to the transdisciplinarity of objects of research by incorporating academic, creative, and activist contributions, disentangles the underlying assumptions of curated cultural narratives about ‘futures worth preserving.’ The volume juxtaposes theories of nostalgia with concepts of sustainability and problematizes their grounding in Western conceptions of time.